Influence of drought stress on growth, biochemical changes and leaf gas exchange of strawberry (Fragaria × ananassa Duch.) in Indonesia - Yenni, Yenni; Ibrahim, Mohd Hafiz; Nulit, Rosimah; Sakimin, Siti Zaharah (AIMS Press, 2022)
Drought stress is one of the challenges that can affect the growth and the quality of strawberry. The study aims to determine the growth, biochemical changes and leaf gas exchange of three strawberry cultivars under drought stress. This study was conducted in a glasshouse at Indonesian Citrus and Subtropical Fruits Research Institute, Indonesia, from July-November 2018. The experiment was arranged in a factorial randomized completely block design (RCBD) with three replications and four water deficit (WD) levels [100% field capacity (FC)/well-watered), 75% of FC (mild WD), 50% of FC (moderate WD), and 25% of FC (severe WD)] for three strawberry cultivars (Earlibrite, California and Sweet Charlie). The results showed that total chlorophyll and anthocyanin contents (p ≤ 0.05) were influenced by the interaction effects of cultivars and water deficit. Whereas other parameters such as plant growth, transpiration rate (E), net photosynthesis (A), stomatal conductance (gs), leaf relative water content (LRWC), flowers and fruits numbers, proline content, length, diameter, weight and total soluble solid (TSS) of fruit were affected by water deficit. A had positive significant correlation with plant height (r = 0.808), leaf area (r = 0.777), fruit length (r = 0.906), fruit diameter (r = 0.889) and fruit weight (r = 0.891). Based on the results, cultivars affected LRWC, and also number of flowers and fruits of the strawberry. This study showed that water deficit decreased plant growth, chlorophyll content, leaf gas exchange, leaf relative water content, length, diameter and weight of fruit but enhanced TSS, anthocyanin, MDA, and proline contents. Increased anthocyanin and proline contents are mechanisms for protecting plants against the effects of water stress. California strawberry had the highest numbers of flowers and fruits, and also anthocyanin content. Hence, this cultivar is recommended to be planted under drought stress conditions. Among all water stress treatments, 75% of FC had the best results to optimize water utilization on the strawberry plants.